Proceedings of the 2017 ACM International Joint Conference on Pervasive and Ubiquitous Computing and Proceedings of the 2017 AC 2017
DOI: 10.1145/3123024.3125617
|View full text |Cite
|
Sign up to set email alerts
|

Supporting smartphone-based behavioral activation

Abstract: Behavioral activation has shown to be a simple yet effective therapy for depressive patients. The method relies on extensive collection of patient reported activity data on an hourly basis. We are currently in the process of designing a smartphone-based behavioral activation system for depressive disorders. However, it is an open question to what degree patients would use this approach given the high demand for user input. In order to investigate this question, we collected paper-based behavioral activation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The ACs consist of 7 distinct classes to cover all types of activities and have been previously presented [ 15 , 16 ]. They were developed in close collaboration with a psychologist by the approach presented in Mørch and Rosenberg and Lejuez et al [ 20 , 21 ] combined with the primary activities introduced in the American Time Use Survey (ATUS) by the Bureau of Labor Statistics [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ACs consist of 7 distinct classes to cover all types of activities and have been previously presented [ 15 , 16 ]. They were developed in close collaboration with a psychologist by the approach presented in Mørch and Rosenberg and Lejuez et al [ 20 , 21 ] combined with the primary activities introduced in the American Time Use Survey (ATUS) by the Bureau of Labor Statistics [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Self-tracking technologies are systems that make use of personal data collection about the sufferers. A majority (19) of papers present novel designs [11,13,17,59,60,60,61,75,77,81,88,89,110,115,120,130,157,163,179], whereas nine [8,15,56,58,90,111,117,148,159] are concerned with methodologies for developing self-tracking technologies attending to the specificities of affective disorders.…”
Section: Analysis Of Reviewed Work System Functionsmentioning
confidence: 99%
“…Regarding reasons for collecting data and sharing with others, seven systems [13,17,60,61,110,115,163] are aimed at encouraging the patient to adhere to a particular course of treatment, a medication prescription or a set of healthy routines, such as exercising. These are often crucial components of any therapy for affective disorders.…”
Section: Analysis Of Reviewed Work System Functionsmentioning
confidence: 99%
“…The inter-categorization agreement was assessed by Cohen's kappa ( ). к The ACs consist of six (+1: 'Other') distinct classes to cover all types of activities and have been previously presented [13,14]. They were developed in close collaboration with a psychologist on the basis of the approach presented in Mørch & Rosenberg and Lejuez et al [18,19] 1.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Recent research has suggested using mobile technology to support BA (e.g., [13][14][15]). This can have several potential benefits.…”
Section: Introductionmentioning
confidence: 99%